Commercial Blocs Geo-economics Study - وفاء كاظم عباس الشمري Wafa'a Abbas Al-Shamary (College of Education for Women, 2018)
The scientific and practical importance of this study lies in analyzing the phenomena of commercial blocs as a means of managing the future struggle as Zbigniew Brzhenski in his book Our of Control which was translated into Arabic under the title of (chaos) in 1993. The most important phenomenon of the 21th century is the geopolitical phenomenon presented by the international blocs. That is, the new regime will be united in the form of economic blocs and political alliance. Consequently, the future struggle will be economic in nature under the chaos which the new order is living.  Under the retreat of the  economy that effected the industrial countries and the world countries which have become unable to treat the crisis issue thy form economic blocs.